2011
DOI: 10.3109/09638288.2010.500344
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception and appraisal of persons with impairments: a randomised controlled field experiment using photo elicitation

Abstract: Signs of stereotypical processing of visual cues of impairment have been found in participants of the Swiss general population. Personal contact with persons with impairments as well as priming participants seems to reduce stereotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been shown that media consumption can cultivate beliefs about reality, and this may be particularly true for those generations which have grown up with the television culture [4]. Moreover, personal contacts and experiences with disabled persons are rather rare in the general population [5], so that the utilisation of latent media knowledge in the assessment of persons with disability and their roles in society is very likely.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that media consumption can cultivate beliefs about reality, and this may be particularly true for those generations which have grown up with the television culture [4]. Moreover, personal contacts and experiences with disabled persons are rather rare in the general population [5], so that the utilisation of latent media knowledge in the assessment of persons with disability and their roles in society is very likely.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot project of the Swiss Paraplegic Research, Reinhardt et al (Reinhardt et al 2010) have recently proposed a new scale to examine the social perception of disability and attitudes towards PwD. The pilot study examined whether visual stimuli of impairment activate latent prejudice against disability and whether this connection can be counteracted with priming strategies (here: a cover story told to the participants).…”
mentioning
confidence: 99%